PECULIARITIES OF THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE SPHERE OF TRADE ENTERPRISE - SHUBA, Tetiana; BOLOTNA, Oksana; LIASHEVSKA, Viktoriia; PRYLYPKO, Andrii; ZHYTCHENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article defines the role of the ethical aspect of introducing artificial intelligence-based technologies into the marketing activities of modern companies. It is established that AI-based marketing relies heavily on the collection and analysis of personal data. The main ethical challenges of using artificial intelligence are identified. Recommendations on how to overcome these challenges are provided. Information and communication technologies (ICT) have significantly transformed human life over the past 60 years. Using the opportunities of the ‘digital revolution’ has allowed some countries to make significant breakthroughs, achieve stable economic growth, and develop national human and technological capital. However, the global spread of ICTs has also led to a number of negative trends and threats that pose risks to sustainable development and the stability of the global economic and political system. Companies that want to remain competitive in the modern era fully understand the importance of information technology in various aspects of their operations. Information technology is no longer seen as a mere tool, but as the basic foundation that enables businesses to operate efficiently and effectively. In every aspect of business, from supply chain management, marketing to customer service, information technology is the foundation that supports various activities. The use of information technology allows companies to automate routine tasks, improve data accuracy and speed up decision-making processes. With quick and easy access to data and information, management can identify opportunities and challenges earlier and thus respond more quickly to market changes. In addition, information technology also allows companies to enhance customer engagement through digital platforms, improve customer experience and increase loyalty.